Elementary and Secondary School Students’ Perceptions of Teachers’ Classroom Management Competencies - Jana Kalin; Cirila Peklaj; Sonja Pečjak; Melita Puklek Levpušček; Milena Valenčič Zuljan (Center for Educational Policy Studies Journal)
Teachers with proper training in knowledge transfer to different students, in the creation of suitable learning conditions, the motivation of students for active cooperation and peer learning, in the formation of classroom community, as well as independent and responsible personalities, can provide quality education. Teacher’s classroom management competencies largely determine the potential of achieving educational goals and helping pupils form integral personalities. Studies show that teachers lack competencies for classroom management and ensuring discipline in the classroom. In the article, we present the results of empirical study on students’ perceptions on teachers’ classroom management competencies in two different subjects, mathematics and Slovene language. A total of 907 students from elementary and secondary schools in Slovenia participated in the study. Differences in students’ assessments have been established in reference to school level and subject. Students’ responses show that secondary school teachers are more focused on achieving educational goals, while aspects of forming a suitable class climate remain less important. The components of quality classroom management (maintenance of supportive learning climate, trusting students) are present in Slovene classes in a larger extent in comparison to maths classes, particularly at the elementary school level. Secondary school students assessed the clarity of rules, student obligations and paying attention in class higher in maths than in Slovene. The results of student’s assessment of teacher competencies imply a need for additional research on teachers’ classroom management competencies in different curriculum subject.